PENERAPAN METODE NAÏVE BAYES DALAM PENENTUAN GIZI PADA IBU HAMIL DI KELURAHAN BUNGA TANJUNG - Depy Rahmadani; Wiwin Handoko; Fuji Sriutami; Khairini Utami Br.Siagian (LPPM STMIK Royal Kisaran, 2023)
Abstract: Nutrition is one of the determinants of the quality of human resources. Food given to pregnant women must contain nutrients as needed, so as to support optimal growth and can prevent malnutrition in pregnant women and also help prevent the occurrence of diseases that can interfere with pregnant women. Determination of good nutrition and malnutrition in pregnant women in the sub-district of Datuk Bandar Timur District, Tanjung Balai City must meet the criteria are age, graphida, body weight, lila, hemoglobin and decision. For pregnant women with normal body weight <25 kg, increased energy intake is needed only after pregnancy to increase the metabolic needs of the mother and the energy needs of the growing fetus. The purpose of this study was to determine good nutrition and malnutrition using the Naïve Bayes method which resulted in a decision on good nutrition and malnutrition in pregnant women. Naive Bayes is a simple probabilistic classifier that calculates a set of probabilities by summing the frequencies and combinations of values from a given dataset. Naïve Bayes produces a Precision value for the positive class of 85%, for the negative class of 86%, the recall value for the positive class is 92%, for the negative class is 75%, the f1-score value for the positive class is 88%, for the negative class is 80%, and 85% for accuracy. Keywords: Machine Learning, Naïve Bayes; Nutritional Status. Abstract: Gizi merupakan salah satu penentu kualitas sumber daya manusia. Makanan yang diberikan pada ibu hamil harus mengandung zat gizi sesuai kebutuhan, sehingga menunjang pertumbuhan yang optimal dan dapat mencegah kurang gizi pada ibu hamil dan juga membantu mencegah timbulnya penyakit-penyakit yang dapat mengganggu ibu hamil. Penentuan gizi baik dan gizi buruk pada ibu hamil di Kelurahan Bunga Tanjung Kecamatan Datuk Bandar Timur, Kota Tanjung Balai harus memenuhi kriteria yaitu umur, grapida, berat badan, lila, hemoglobin dan keputusan. Untuk ibu hamil dengan berat badan normal <25 kg, peningkatan asupan energi diperlukan hanya setelah kehamilan untuk meningkatkan kebutuhan metabolisme yang dibutuhkan ibu dan kebutuhan energi janin yang sedang tumbuh. Tujuan penelitian ini untuk penentuan gizi baik dan gizi buruk dengan menggunakan metode naïve bayes yang menghasilkan sebuah keputusan gizi baik dan gizi buruk pada ibu hamil. Naive Bayes merupakan sebuah pengklasifikasian probabilistik sederhana yang menghitung sekumpulan probabilitas dengan menjumlahkan frekuensi dan kombinasi nilai dari dataset yang diberikan. Naïve Bayes menghasilkan nilai Precision untuk kelas positif 85%, untuk kelas negatif 86%, nilai recall untuk kelas positif 92%, untuk kelas negatif 75%, nilai f1-score untuk kelas positif 88%, untuk kelas negatif sebesar 80%, dan nilai akurasi 85%. Kata Kunci: Machine Learning; Naïve Bayes; Status Gizi.